2003
DOI: 10.1103/physrevlett.90.257002
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Charge-Density-Wave State inSr14Cu24O41by Calcium Doping

Abstract: The charge response in the spin chain/ladder compound Sr14−xCaxCu24O41 is characterized by DC resistivity, low-frequency dielectric spectroscopy and optical spectroscopy. We identify a phase transition below which a charge-density wave (CDW) develops in the ladder arrays. Calcium doping suppresses this phase with the transition temperature decreasing from 210 K for x = 0 to 10 K for x = 9, and the CDW gap from 130 meV down to 3 meV, respectively. This suppression is due to the worsened nesting originating from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 21 publications
15
71
0
Order By: Relevance
“…We remark that this normalization yields the correct estimate of the mass change at the uniform variation of the coupling constants. Indeed, in this case, according to (59), the change of the effective coupling at energy m is δg 0 /g 2 0 and (52) gives δm ∼ δg 0 /g 2 0 m. On the other hand we obtain the same estimate from the known dependence of the mass on the bare coupling:…”
Section: First Order Effects: Perturbations Around the O(6)-symmetsupporting
confidence: 72%
See 1 more Smart Citation
“…We remark that this normalization yields the correct estimate of the mass change at the uniform variation of the coupling constants. Indeed, in this case, according to (59), the change of the effective coupling at energy m is δg 0 /g 2 0 and (52) gives δm ∼ δg 0 /g 2 0 m. On the other hand we obtain the same estimate from the known dependence of the mass on the bare coupling:…”
Section: First Order Effects: Perturbations Around the O(6)-symmetsupporting
confidence: 72%
“…However, according to Ref. 59, the values of the CDW gaps at x = 0, 3 and 9 are 130 meV, 110 meV and 3 meV respectively which is either several times larger or much smaller than the spin gap. From this analysis we conclude that though detailed comparison between theory and experiment would be premature, the field theory description of telephone number compound is a reasonable approach ( as far as the system remains strongly one-dimensional which probably corresponds to x < 9).…”
Section: Discussionmentioning
confidence: 87%
“…7 Since the interaction process between electrons near Fermi points is considered to play an important role for weak coupling, the integral over q in Eq. (4.16) can safely be split into two parts, 17) where (T −1 1 ) uni and (T −1 1 ) stag are the contributions from small q and large q , respectively. Thus (T −1 1 ) uni denotes the uniform contribution to the NMR relaxation rate, while (T −1 1 ) stag is the antiferromagnetic staggered contribution.…”
Section: B Nmr Relaxation Ratementioning
confidence: 99%
“…In addition to the superconducting state, intensive studies have been devoted to the charge-density-wave (CDW) state, which is found in the parent system (x = 0) from optical measurements. 13,14,15 Further the global phase diagram for overall hole doping 16,17 shows that, with increasing the hole doping, the CDW state is suppressed and disappears at x ≃ 9, while the superconducting state emerges for x ≃ 11 and under pressure. From Raman scattering measurements, 18 it has been suggested that collective modes of the CDW state exist even in the highly doped superconducting material x = 12.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that a similar 2D dispersion was previously observed in the CDW phase developed in the ladder layers of Sr 14 Cu 24 O 41 . [54][55][56] Calculations based on the extended Hubbard model and the t-J model predicted sinusoidal charge-density modulation either of 2k F or 4k F type for this system. [57][58][59] This result was at first met with surprise due to the strongly correlated nature of the ladders system.…”
mentioning
confidence: 99%